16. CURRENT STATUS OF BREASTFEEDING WOMEN AFTER GIVING BIRTH DURING HOSPITAL STAY AT THE OBSTETRICS DEPARTMENT OF HAPPY INTERNATIONAL HOSPITAL, BINH DUONG PROVINCE, IN 2022 AND SOME RELATED (Vietnam Journal of Community Medicine, 2023)
Objectives: Describe the status of breastfeeding mothers after giving birth during their hospital stayat the Department of Obstetrics and Gynecology at Hanh Phuc International Hospital, Binh Duongprovince and analyze some related factors.Research method: An analytical cross-sectional study was performed on 270 vaginal and cesareandeliveries, using a checklist of early breastfeeding and breastfeeding during the hospital stay andinterviews to identify associated factors.Results: The rate of infants being breastfed early in the first hour after birth reached 86.7%, andthe rate of infants exclusively breastfed during the hospital stay was 57.8%; Some of the factorslinked to early breastfeeding after birth are maternal education, pre-pregnancy, antenatal classes, anddelivery method. Some factors related to exclusive breastfeeding during library time are attendingpre-production and birth methods classes, having family support, and breastfeeding properly.Conclusion: The majority of mothers giving birth at Hanh Phuc International Hospital have startedbreastfeeding their babies soon after birth, but the percentage of mothers who exclusively breastfeedtheir babies during their postnatal hospital stay is not high.The rate of exclusive breastfeeding during the postpartum hospital stay in the group that participatedin antenatal training was 1.2 times higher than that in the group that did not receive the training. Therate of exclusive breastfeeding during the postpartum hospital stay was lower in the cesarean sectionthan in the vaginal delivery group. The rate of exclusive breastfeeding during postpartum hospitalstay was 1.97 times higher in the group with family help in breastfeeding compared to the groupwithout help…
Keywords: Exclusive breastfeeding, maternity, Hanh Phuc International Hospital.